Indian demographic and food prospects: state level analysis - Dyson, Tim; Hanchate, Amresh (2000)
This paper is a state-level analysis of India's demographic and food prospects. The first part of the paper that contains new population projections argues that future demographic growth will probably be a little less than estimated although the country's population will still go on to exceed 1.5 billion. The second part of the paper assesses the future demand for cereals and other foods in 2020 and concludes that the real production challenge relates to vegetables, fruit and milk. - Reproduced
Keywords: Food resources - India; India - Population; Population projections